Stratigraphy, mineralogy and geochemistry of the Upper Laetolil tuffs including a new tuff 7 site with footprints of Australopithecus afarensis, Laetoli, Tanzania. (October 2019) - Zaitsev, Anatoly N.; McHenry, Lindsay; Savchenok, Anton I.; Strekopytov, Stanislav; Spratt, John; Humphreys-Williams, Emma; Sharygin, Victor V.; Bogomolov, Evgeny S.; Chakhmouradian, Anton R.; Zaitseva, Olga A.; Arzamastsev, Andrei A.; Reguir, Ekaterina P.; et al.
Abstract: The Upper Laetolil marker Tuffs 1 to 8 are mineralogically similar rocks, but heterogeneous in terms of their texture, structure, proportion of primary minerals, volume of cement and degree of low-temperature alteration. Originally they were deposited as crystal and/or vitric ash of evolved melilite-nephelinitic composition and not as melilitite-(natro)carbonatite. Occurrence of carbonate-silicate melt inclusions in primary minerals supports R. Hay's conclusion that the ash could have erupted from a carbonatitic volcanic source. Primary minerals (melilite, clinopyroxene, garnet, perovskite, magnetite) in the tuffs are characterised by wide variations in their compositions and two and even more mineral populations are present within each marker tuff. Thus, any correlation between the tuffs from different localities on the basis of mineral composition is very difficult to impossible. Tuff 7, with footprints of Australopithecus afarensis, is a very heterogeneous unit both vertically and laterally that formed during four major eruption events. Trace-element geochemistry and Sr–Nd isotopic data for Tuffs 6, 7 and 8 suggest that compositionally different volcanic sources were involved in their formation. Initial 87 Sr/ 86 Sr and 144 Nd/ 143 Nd ratios also show that the Sadiman volcano should not be considered as a source for these three marker tuffs at Laetoli. Only Essimingor and Mosonik volcanoes produced rocks that are mineralogically and geochemically similar to the Upper Laetolil marker tuffs, though these volcanoes lie about 100 km from Laetoli. Highlights: Upper Laetolil marker Tuffs are heterogeneous rocks. Composition of primary minerals cannot be used for tuffs correlation. Tuff 7 with Australopithecus afarensis footprints was formed during four major eruption events. Original volcanic source is considered to be evolved carbonate-bearing melilite nephelinite.